Integrated coastal zone management of coral reefs : decision support modeling - Gustavson, Kent, 1967-; Huber, Richard M., 1954-; Ruitenbeek, H. Jack.; World Bank. (Washington, D.C. : World Bank, 2000)
This research indicates that, to improve awareness, park education programs should be targeted specifically to the user groups primarily through outreach programs. Further, the Park's management programs should be highlighted, particularly the beneficial, tangible products and services (benefits) the Park provides to each user group
One folded colored map inserted.
Includes bibliographical references (p. [271]-289).
oif 18/08/15
Loan
Keywords: Coral reef management -- Decision making -- Case studies; Integrated coastal zone management -- Decision making -- Case studies